Analisis Perceived Risk, Trust, Price Terhadap Online Purchase Intention dengan Attitude sebagai Variabel Intervening pada Gen Z di Kota Surabaya - Muhammad Burhanuddin Thobari; Regita Cahyani; Siti Mujanah; Achmad Yanu Alif Fianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In the development of digitalization, online shopping is the main choice for consumers, especially generation Z in Surabaya City. However, online purchasing decisions are still influenced by several factors such as perceived risk, trust, price, and consumer attitudes. Therefore, it is important to understand the influence of these factors on online purchase intentions in this generation. This study aims to analyze the effect of Perceived Risk, Trust, and Price on Online Purchase Intention with Attitude as an intervening variable in generation Z in Surabaya City. This research uses quantitative methods with purposive random sampling techniques. The sample consisted of 100 Gen Z respondents in Surabaya City. The data was collected using a questionnaire that had been tested for validity and reliability, and analyzed using IBM SPSS STATISTIK 25 path analysis. The results showed that Perceived Risk, Trust, and Price have a significant effect on Online Purchase Intention directly or indirectly through Attitude as an intervening variable. Consumer trust plays an important role in strengthening positive attitudes towards online shopping, while perceived risk has a negative effect on purchase intention. Consumer attitudes play an important role in mediating the influence of Perceived Risk, Trust, and Price on Gen Z online purchase intentions. Increasing trust and decreasing perceived risk can increase Gen Z's intention to make online purchases.